Dinamika Peran Ulama dalam Perpolitikan Nasional Pasca-Orde Baru - Basyar, M. Hamdan (Jurnal Penelitian Politik, 2008)
In Indonesian national politics the ulenta clerics can be categorized in three groups First are those who percieved that religious and social Life cannot be separated There is no such separation in Islam Therefore they think that the involvement of ulema in a daily political matters is an obligation This group of ulerna play significant role and actively involved in political party Second those who also think that religious and social life including politics cannot be separated But they think it is not necessary for them to involve in political practice This group of ulenta even they concern with political and statehood problem they do not play as opponents of one of political party openly In the election this group of ulema participate to vote one of contestant but they do not participate in one of political party campaign Third those who do not care with political life They think that political life is not their significant concern This group limit their role only in moral religious matters They avoid political life as then think that it is too material world.